A pan-cancer analysis of the role of USP5 in human cancers - Yan, Bokang; Guo, Jiaxing; Deng, Shuang; Chen, Dongliang; Huang, Meiyuan (Scientific reports, 2023)
Posttranslational modifications (PTM) such as acetylation, deubiquitination, and phosphorylation of proteins, play important roles in various kinds of cancer progression. Ubiquitin-specific proteinase 5 (USP5), a unique member of deubiquitinating enzymes (DUBs) which recognizes unanchored polyubiquitin specifically, could regulate the stability of many tumorigenesis-associated proteins to influence cancer initiation and progression. However, the diverse biological significance of USP5 in pan-cancer has not been systematically and comprehensively studied. Here, we explored the role of USP5 in pan-cancer using The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) database, and we also acquired and analyzed data via various software and web platforms such as R, GEPIA2.0, HPA, TISIDB, cBioPortal, UALCAN, TIMER 2.0, CancerSEA and BioGRID. USP5 expression was high in most cancers and differed significantly in different molecular and immune subtypes of cancers. In addition, USP5 had certain diagnostic value in multiple cancers, and high expression of USP5 generally predicted poor prognosis for cancer patients. We also found that the most frequent genetic alterations type of USP5 was mutation, and the DNA methylation level of USP5 decreased in various cancers. Furthermore, USP5 expression correlated with cancer-associated fibroblasts (CAFs), endothelial cells (EC) and genetic markers of immunodulators in cancers. Moreover, the result from single cell sequencing showed that USP5 could regulate several tumor biological behaviors such as apoptosis, DNA damage and metastasis. Gene enrichment analysis indicated “spliceosome” and “RNA splicing” may be the critical mechanism for USP5 to involve in cancer. Taken together, our study elucidates the biological significance of USP5 in the diagnosis, prognosis and immune in human pan-cancer.